Wolff-Parkinson-White syndrome: De novo variants and evidence for mutational burden in genes associated with atrial fibrillation. - Coban-Akdemir, Zeynep H; Charng, Wu-Lin; Azamian, Mahshid; Paine, Ingrid S; Punetha, Jaya; Grochowski, Christopher M; Gambin, Tomasz; Valdes, Santiago O; Cannon, Bryan; Zapata, Gladys; Hernandez, Patricia P; Jhangiani, Shalini; et al. (Am J Med Genet A, 2020)
BACKGROUND: Wolff-Parkinson-White (WPW) syndrome is a relatively common arrhythmia affecting ~1-3/1,000 individuals. Mutations in PRKAG2 have been described in rare patients in association with cardiomyopathy. However, the genetic basis of WPW in individuals with a structurally normal heart remains poorly understood. Sudden death due to atrial fibrillation (AF) can also occur in these individuals. Several studies have indicated that despite ablation of an accessory pathway, the risk of AF remains high in patients compared to general population. METHODS: We applied exome sequencing in 305 subjects, including 65 trios, 80 singletons, and 6 multiple affected families. We used de novo analysis, candidate gene approach, and burden testing to explore the genetic contributions to WPW. RESULTS: A heterozygous deleterious variant in PRKAG2 was identified in one subject, accounting for 0.6% (1/151) of the genetic basis of WPW in this study. Another individual with WPW and left ventricular hypertrophy carried a known pathogenic variant in MYH7. We found rare de novo variants in genes associated with arrhythmia and cardiomyopathy (ANK2, NEBL, PITX2, and PRDM16) in this cohort. There was an increased burden of rare deleterious variants (MAF ≤ 0.005) with CADD score ≥ 25 in genes linked to AF in cases compared to controls (P = .0023). CONCLUSIONS: Our findings show an increased burden of rare deleterious variants in genes linked to AF in WPW syndrome, suggesting that genetic factors that determine the development of accessory pathways may be linked to an increased susceptibility of atrial muscle to AF in a subset of patients.
Keywords: Adolescent; Adult; AMP-Activated Protein Kinases; Ankyrins; Atrial Fibrillation; Carrier Proteins; Child; Cohort Studies; Cytoskeletal Proteins; DNA-Binding Proteins; Female; Genetic Association Studies; Genetic Predisposition to Disease; Heart Atria; Homeodomain Proteins; Humans; LIM Domain Proteins; Male; Mutation; Transcription Factors; Whole Exome Sequencing; Wolff-Parkinson-White Syndrome; Young Adult

ZMIZ1 Variants Cause a Syndromic Neurodevelopmental Disorder. - Carapito, Raphael; Ivanova, Ekaterina L; Morlon, Aurore; Meng, Linyan; Molitor, Anne; Erdmann, Eva; Kieffer, Bruno; Pichot, Angélique; Naegely, Lydie; Kolmer, Aline; Paul, Nicodème; Hanauer, Antoine; et al. (Am J Hum Genet, 2019)
ZMIZ1 is a coactivator of several transcription factors, including p53, the androgen receptor, and NOTCH1. Here, we report 19 subjects with intellectual disability and developmental delay carrying variants in ZMIZ1. The associated features include growth failure, feeding difficulties, microcephaly, facial dysmorphism, and various other congenital malformations. Of these 19, 14 unrelated subjects carried de novo heterozygous single-nucleotide variants (SNVs) or single-base insertions/deletions, 3 siblings harbored a heterozygous single-base insertion, and 2 subjects had a balanced translocation disrupting ZMIZ1 or involving a regulatory region of ZMIZ1. In total, we identified 13 point mutations that affect key protein regions, including a SUMO acceptor site, a central disordered alanine-rich motif, a proline-rich domain, and a transactivation domain. All identified variants were absent from all available exome and genome databases. In vitro, ZMIZ1 showed impaired coactivation of the androgen receptor. In vivo, overexpression of ZMIZ1 mutant alleles in developing mouse brains using in utero electroporation resulted in abnormal pyramidal neuron morphology, polarization, and positioning, underscoring the importance of ZMIZ1 in neural development and supporting mutations in ZMIZ1 as the cause of a rare neurodevelopmental syndrome.
Keywords: Alleles; Animals; Child; Child, Preschool; Developmental Disabilities; Female; Humans; Infant; Intellectual Disability; Male; Mice; Point Mutation; Syndrome; Transcription Factors

Clinically severe CACNA1A alleles affect synaptic function and neurodegeneration differentially. - Luo, Xi; Rosenfeld, Jill A; Yamamoto, Shinya; Harel, Tamar; Zuo, Zhongyuan; Hall, Melissa; Wierenga, Klaas J; Pastore, Matthew T; Bartholomew, Dennis; Delgado, Mauricio R; Rotenberg, Joshua; Lewis, Richard Alan; et al. (PLoS Genet, 2017)
Dominant mutations in CACNA1A, encoding the α-1A subunit of the neuronal P/Q type voltage-dependent Ca2+ channel, can cause diverse neurological phenotypes. Rare cases of markedly severe early onset developmental delay and congenital ataxia can be due to de novo CACNA1A missense alleles, with variants affecting the S4 transmembrane segments of the channel, some of which are reported to be loss-of-function. Exome sequencing in five individuals with severe early onset ataxia identified one novel variant (p.R1673P), in a girl with global developmental delay and progressive cerebellar atrophy, and a recurrent, de novo p.R1664Q variant, in four individuals with global developmental delay, hypotonia, and ophthalmologic abnormalities. Given the severity of these phenotypes we explored their functional impact in Drosophila. We previously generated null and partial loss-of-function alleles of cac, the homolog of CACNA1A in Drosophila. Here, we created transgenic wild type and mutant genomic rescue constructs with the two noted conserved point mutations. The p.R1673P mutant failed to rescue cac lethality, displayed a gain-of-function phenotype in electroretinograms (ERG) recorded from mutant clones, and evolved a neurodegenerative phenotype in aging flies, based on ERGs and transmission electron microscopy. In contrast, the p.R1664Q variant exhibited loss of function and failed to develop a neurodegenerative phenotype. Hence, the novel R1673P allele produces neurodegenerative phenotypes in flies and human, likely due to a toxic gain of function.
Keywords: Alleles; Animals; Animals, Genetically Modified; Calcium Channels; Cerebellar Ataxia; Child; Child, Preschool; Drosophila melanogaster; Female; Genome, Human; Genome-Wide Association Study; Humans; Male; Microscopy, Electron, Transmission; Mutation, Missense; Neurodegenerative Diseases; Neuroimaging; Phenotype; Point Mutation

Congenital heart defects and left ventricular non-compaction in males with loss-of-function variants in NONO. - Scott, Daryl A; Hernandez-Garcia, Andres; Azamian, Mahshid S; Jordan, Valerie K; Kim, Bum Jun; Starkovich, Molly; Zhang, Jinglan; Wong, Lee-Jun; Darilek, Sandra A; Breman, Amy M; Yang, Yaping; Lupski, James R; et al. (J Med Genet, 2017)
BACKGROUND: The non-POU domain containing octamer-binding gene (NONO) is located on chromosome Xq13.1 and encodes a member of a small family of RNA-binding and DNA-binding proteins that perform a variety of tasks involved in RNA synthesis, transcriptional regulation and DNA repair. Loss-of-function variants in NONO have been described as a cause of intellectual disability in males but have not been described in association with congenital heart defects or cardiomyopathy. In this article, we seek to further define the phenotypic consequences of NONO depletion in human subjects. METHODS: We searched a clinical database of over 6000 individuals referred for exome sequencing and over 60 000 individuals referred for CNV analysis. RESULTS: We identified two males with atrial and ventricular septal defects, left ventricular non-compaction (LVNC), developmental delay and intellectual disability, who harboured de novo, loss-of-function variants in NONO. We also identified a male infant with developmental delay, congenital brain anomalies and severe LVNC requiring cardiac transplantation, who inherited a single-gene deletion of NONO from his asymptomatic mother. CONCLUSIONS: We conclude that in addition to global developmental delay and intellectual disability, males with loss-of-function variants in NONO may also be predisposed to developing congenital heart defects and LVNC with the penetrance of these cardiac-related problems being influenced by genetic, epigenetic, environmental or stochastic factors. Brain imaging of males with NONO deficiency may reveal structural defects with abnormalities of the corpus callosum being the most common. Although dysmorphic features vary between affected individuals, relative macrocephaly is a common feature.
Keywords: Child; Child, Preschool; Developmental Disabilities; DNA-Binding Proteins; Exome; Heart Defects, Congenital; Heart Ventricles; Humans; Infant; Male; Nuclear Matrix-Associated Proteins; Octamer Transcription Factors; RNA-Binding Proteins

An exome sequencing study of Moebius syndrome including atypical cases reveals an individual with CFEOM3A and a mutation. - Patel, Ronak M; Liu, David; Gonzaga-Jauregui, Claudia; Jhangiani, Shalini; Lu, James T; Sutton, V Reid; Fernbach, Susan D; Azamian, Mahshid; White, Lisa; Edmond, Jane C; Paysse, Evelyn A; Belmont, John W; et al. (Cold Spring Harb Mol Case Stud, 2017)
Moebius syndrome is characterized by congenital unilateral or bilateral facial and abducens nerve palsies (sixth and seventh cranial nerves) causing facial weakness, feeding difficulties, and restricted ocular movements. Abnormalities of the chest wall such as Poland anomaly and variable limb defects are frequently associated with this syndrome. Most cases are isolated; however, rare families with autosomal dominant transmission with incomplete penetrance and variable expressivity have been described. The genetic basis of this condition remains unknown. In a cohort study of nine individuals suspected to have Moebius syndrome (six typical, three atypical), we performed whole-exome sequencing to try to identify a commonly mutated gene. Although no such gene was identified and we did not find mutations in and , we found a de novo heterozygous mutation, p.E410K, in the gene encoding tubulin beta 3 class III (), in an individual with atypical Moebius syndrome. This individual was diagnosed with near-complete ophthalmoplegia, agenesis of the corpus callosum, and absence of the septum pellucidum. No substantial limb abnormalities were noted. Mutations in have been associated with complex cortical dysplasia and other brain malformations and congenital fibrosis of extraocular muscles type 3A (CFEOM3A). Our report highlights the overlap of genetic etiology and clinical differences between CFEOM and Moebius syndrome and describes our approach to identifying candidate genes for typical and atypical Moebius syndrome.
Keywords: Child; Child, Preschool; Cohort Studies; Exome; Eye Diseases, Hereditary; Facial Paralysis; Female; Humans; Infant; Male; Malformations of Cortical Development; Mobius Syndrome; Muscular Diseases; Mutation; Ocular Motility Disorders; Ophthalmoplegia; Orbital Diseases; Pedigree; Tubulin; Whole Exome Sequencing

Haploinsufficiency of the E3 ubiquitin-protein ligase gene TRIP12 causes intellectual disability with or without autism spectrum disorders, speech delay, and dysmorphic features. - Zhang, Jing; Gambin, Tomasz; Yuan, Bo; Szafranski, Przemyslaw; Rosenfeld, Jill A; Balwi, Mohammed Al; Alswaid, Abdulrahman; Al-Gazali, Lihadh; Shamsi, Aisha M Al; Komara, Makanko; Ali, Bassam R; Roeder, Elizabeth; et al. (Hum Genet, 2017)
Impairment of ubiquitin-proteasome system activity involving ubiquitin ligase genes UBE3A, UBE3B, and HUWE1 and deubiquitinating enzyme genes USP7 and USP9X has been reported in patients with neurodevelopmental delays. To date, only a handful of single-nucleotide variants (SNVs) and copy-number variants (CNVs) involving TRIP12, encoding a member of the HECT domain E3 ubiquitin ligases family on chromosome 2q36.3 have been reported. Using chromosomal microarray analysis and whole-exome sequencing (WES), we have identified, respectively, five deletion CNVs and four inactivating SNVs (two frameshifts, one missense, and one splicing) in TRIP12. Seven of these variants were found to be de novo; parental studies could not be completed in two families. Quantitative PCR analyses of the splicing mutation showed a dramatically decreased level of TRIP12 mRNA in the proband compared to the family controls, indicating a loss-of-function mechanism. The shared clinical features include intellectual disability with or without autistic spectrum disorders, speech delay, and facial dysmorphism. Our findings demonstrate that E3 ubiquitin ligase TRIP12 plays an important role in nervous system development and function. The nine presented pathogenic variants further document that TRIP12 haploinsufficiency causes a childhood-onset neurodevelopmental disorder. Finally, our data enable expansion of the phenotypic spectrum of ubiquitin-proteasome dependent disorders.
Keywords: Adolescent; Autism Spectrum Disorder; Carrier Proteins; Child; Child, Preschool; Cohort Studies; DNA Copy Number Variations; Facies; Female; Haploinsufficiency; Humans; Infant; Intellectual Disability; Language Development Disorders; Male; Ubiquitin-Protein Ligases

High Rate of Recurrent De Novo Mutations in Developmental and Epileptic Encephalopathies. - Hamdan, Fadi F; Myers, Candace T; Cossette, Patrick; Lemay, Philippe; Spiegelman, Dan; Laporte, Alexandre Dionne; Nassif, Christina; Diallo, Ousmane; Monlong, Jean; Cadieux-Dion, Maxime; Dobrzeniecka, Sylvia; Meloche, Caroline; et al. (Am J Hum Genet, 2017)
Developmental and epileptic encephalopathy (DEE) is a group of conditions characterized by the co-occurrence of epilepsy and intellectual disability (ID), typically with developmental plateauing or regression associated with frequent epileptiform activity. The cause of DEE remains unknown in the majority of cases. We performed whole-genome sequencing (WGS) in 197 individuals with unexplained DEE and pharmaco-resistant seizures and in their unaffected parents. We focused our attention on de novo mutations (DNMs) and identified candidate genes containing such variants. We sought to identify additional subjects with DNMs in these genes by performing targeted sequencing in another series of individuals with DEE and by mining various sequencing datasets. We also performed meta-analyses to document enrichment of DNMs in candidate genes by leveraging our WGS dataset with those of several DEE and ID series. By combining these strategies, we were able to provide a causal link between DEE and the following genes: NTRK2, GABRB2, CLTC, DHDDS, NUS1, RAB11A, GABBR2, and SNAP25. Overall, we established a molecular diagnosis in 63/197 (32%) individuals in our WGS series. The main cause of DEE in these individuals was de novo point mutations (53/63 solved cases), followed by inherited mutations (6/63 solved cases) and de novo CNVs (4/63 solved cases). De novo missense variants explained a larger proportion of individuals in our series than in other series that were primarily ascertained because of ID. Moreover, these DNMs were more frequently recurrent than those identified in ID series. These observations indicate that the genetic landscape of DEE might be different from that of ID without epilepsy.
Keywords: Brain Diseases; Child; Child, Preschool; Epilepsy; Female; Genome, Human; Genome-Wide Association Study; Humans; Intellectual Disability; Male; Mutation; Recurrence; Seizures

Identification of novel candidate disease genes from de novo exonic copy number variants. - Gambin, Tomasz; Yuan, Bo; Bi, Weimin; Liu, Pengfei; Rosenfeld, Jill A; Coban-Akdemir, Zeynep; Pursley, Amber N; Nagamani, Sandesh C S; Marom, Ronit; Golla, Sailaja; Dengle, Lauren; Petrie, Heather G; et al. (Genome Med, 2017)
BACKGROUND: Exon-targeted microarrays can detect small (<1000 bp) intragenic copy number variants (CNVs), including those that affect only a single exon. This genome-wide high-sensitivity approach increases the molecular diagnosis for conditions with known disease-associated genes, enables better genotype-phenotype correlations, and facilitates variant allele detection allowing novel disease gene discovery. METHODS: We retrospectively analyzed data from 63,127 patients referred for clinical chromosomal microarray analysis (CMA) at Baylor Genetics laboratories, including 46,755 individuals tested using exon-targeted arrays, from 2007 to 2017. Small CNVs harboring a single gene or two to five non-disease-associated genes were identified; the genes involved were evaluated for a potential disease association. RESULTS: In this clinical population, among rare CNVs involving any single gene reported in 7200 patients (11%), we identified 145 de novo autosomal CNVs (117 losses and 28 intragenic gains), 257 X-linked deletion CNVs in males, and 1049 inherited autosomal CNVs (878 losses and 171 intragenic gains); 111 known disease genes were potentially disrupted by de novo autosomal or X-linked (in males) single-gene CNVs. Ninety-one genes, either recently proposed as candidate disease genes or not yet associated with diseases, were disrupted by 147 single-gene CNVs, including 37 de novo deletions and ten de novo intragenic duplications on autosomes and 100 X-linked CNVs in males. Clinical features in individuals with de novo or X-linked CNVs encompassing at most five genes (224 bp to 1.6 Mb in size) were compared to those in individuals with larger-sized deletions (up to 5 Mb in size) in the internal CMA database or loss-of-function single nucleotide variants (SNVs) detected by clinical or research whole-exome sequencing (WES). This enabled the identification of recently published genes (BPTF, NONO, PSMD12, TANGO2, and TRIP12), novel candidate disease genes (ARGLU1 and STK3), and further confirmation of disease association for two recently proposed disease genes (MEIS2 and PTCHD1). Notably, exon-targeted CMA detected several pathogenic single-exon CNVs missed by clinical WES analyses. CONCLUSIONS: Together, these data document the efficacy of exon-targeted CMA for detection of genic and exonic CNVs, complementing and extending WES in clinical diagnostics, and the potential for discovery of novel disease genes by genome-wide assay.
Keywords: Cohort Studies; DNA Copy Number Variations; Exons; Genetic Diseases, Inborn; Genome, Human; Homeodomain Proteins; Humans; Intracellular Signaling Peptides and Proteins; Membrane Proteins; Neurodevelopmental Disorders; Protein-Serine-Threonine Kinases; Retrospective Studies; Transcription Factors; Whole Genome Sequencing

Lessons learned from additional research analyses of unsolved clinical exome cases. - Eldomery, Mohammad K; Coban-Akdemir, Zeynep; Harel, Tamar; Rosenfeld, Jill A; Gambin, Tomasz; Stray-Pedersen, Asbjørg; Küry, Sébastien; Mercier, Sandra; Lessel, Davor; Denecke, Jonas; Wiszniewski, Wojciech; Penney, Samantha; et al. (Genome Med, 2017)
BACKGROUND: Given the rarity of most single-gene Mendelian disorders, concerted efforts of data exchange between clinical and scientific communities are critical to optimize molecular diagnosis and novel disease gene discovery. METHODS: We designed and implemented protocols for the study of cases for which a plausible molecular diagnosis was not achieved in a clinical genomics diagnostic laboratory (i.e. unsolved clinical exomes). Such cases were recruited to a research laboratory for further analyses, in order to potentially: (1) accelerate novel disease gene discovery; (2) increase the molecular diagnostic yield of whole exome sequencing (WES); and (3) gain insight into the genetic mechanisms of disease. Pilot project data included 74 families, consisting mostly of parent-offspring trios. Analyses performed on a research basis employed both WES from additional family members and complementary bioinformatics approaches and protocols. RESULTS: Analysis of all possible modes of Mendelian inheritance, focusing on both single nucleotide variants (SNV) and copy number variant (CNV) alleles, yielded a likely contributory variant in 36% (27/74) of cases. If one includes candidate genes with variants identified within a single family, a potential contributory variant was identified in a total of ~51% (38/74) of cases enrolled in this pilot study. The molecular diagnosis was achieved in 30/63 trios (47.6%). Besides this, the analysis workflow yielded evidence for pathogenic variants in disease-associated genes in 4/6 singleton cases (66.6%), 1/1 multiplex family involving three affected siblings, and 3/4 (75%) quartet families. Both the analytical pipeline and the collaborative efforts between the diagnostic and research laboratories provided insights that allowed recent disease gene discoveries (PURA, TANGO2, EMC1, GNB5, ATAD3A, and MIPEP) and increased the number of novel genes, defined in this study as genes identified in more than one family (DHX30 and EBF3). CONCLUSION: An efficient genomics pipeline in which clinical sequencing in a diagnostic laboratory is followed by the detailed reanalysis of unsolved cases in a research environment, supplemented with WES data from additional family members, and subject to adjuvant bioinformatics analyses including relaxed variant filtering parameters in informatics pipelines, can enhance the molecular diagnostic yield and provide mechanistic insights into Mendelian disorders. Implementing these approaches requires collaborative clinical molecular diagnostic and research efforts.
Keywords: Adenosine Triphosphatases; ATPases Associated with Diverse Cellular Activities; Computational Biology; DNA Copy Number Variations; DNA-Binding Proteins; Exome; Female; Genetic Diseases, Inborn; Genomics; GTP-Binding Protein beta Subunits; Humans; Male; Membrane Proteins; Metalloendopeptidases; Mitochondrial Proteins; Pilot Projects; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; Transcription Factors

Phenotypic and molecular characterisation of CDK13-related congenital heart defects, dysmorphic facial features and intellectual developmental disorders. - Bostwick, Bret L; McLean, Scott; Posey, Jennifer E; Streff, Haley E; Gripp, Karen W; Blesson, Alyssa; Powell-Hamilton, Nina; Tusi, Jessica; Stevenson, David A; Farrelly, Ellyn; Hudgins, Louanne; Yang, Yaping; et al. (Genome Med, 2017)
BACKGROUND: De novo missense variants in CDK13 have been described as the cause of syndromic congenital heart defects in seven individuals ascertained from a large congenital cardiovascular malformations cohort. We aimed to further define the phenotypic and molecular spectrum of this newly described disorder. METHODS: To minimise ascertainment bias, we recruited nine additional individuals with CDK13 pathogenic variants from clinical and research exome laboratory sequencing cohorts. Each individual underwent dysmorphology exam and comprehensive medical history review. RESULTS: We demonstrate greater than expected phenotypic heterogeneity, including 33% (3/9) of individuals without structural heart disease on echocardiogram. There was a high penetrance for a unique constellation of facial dysmorphism and global developmental delay, as well as less frequently seen renal and sacral anomalies. Two individuals had novel CDK13 variants (p.Asn842Asp, p.Lys734Glu), while the remaining seven unrelated individuals had a recurrent, previously published p.Asn842Ser variant. Summary of all variants published to date demonstrates apparent restriction of pathogenic variants to the protein kinase domain with clustering in the ATP and magnesium binding sites. CONCLUSIONS: Here we provide detailed phenotypic and molecular characterisation of individuals with pathogenic variants in CDK13 and propose management guidelines based upon the estimated prevalence of anomalies identified.
Keywords: Adolescent; Adult; CDC2 Protein Kinase; Child; Child, Preschool; Face; Female; Heart Defects, Congenital; Humans; Infant; Intellectual Disability; Male; Mutation; Phenotype; Syndrome

Use of Exome Sequencing for Infants in Intensive Care Units: Ascertainment of Severe Single-Gene Disorders and Effect on Medical Management. - Meng, Linyan; Pammi, Mohan; Saronwala, Anirudh; Magoulas, Pilar; Ghazi, Andrew Ray; Vetrini, Francesco; Zhang, Jing; He, Weimin; Dharmadhikari, Avinash V; Qu, Chunjing; Ward, Patricia; Braxton, Alicia; et al. (JAMA Pediatr, 2017)
Importance: While congenital malformations and genetic diseases are a leading cause of early infant death, to our knowledge, the contribution of single-gene disorders in this group is undetermined. Objective: To determine the diagnostic yield and use of clinical exome sequencing in critically ill infants. Design, Setting, and Participants: Clinical exome sequencing was performed for 278 unrelated infants within the first 100 days of life who were admitted to Texas Children's Hospital in Houston, Texas, during a 5-year period between December 2011 and January 2017. Exome sequencing types included proband exome, trio exome, and critical trio exome, a rapid genomic assay for seriously ill infants. Main Outcomes and Measures: Indications for testing, diagnostic yield of clinical exome sequencing, turnaround time, molecular findings, patient age at diagnosis, and effect on medical management among a group of critically ill infants who were suspected to have genetic disorders. Results: The mean (SEM) age for infants participating in the study was 28.5 (1.7) days; of these, the mean (SEM) age was 29.0 (2.2) days for infants undergoing proband exome sequencing, 31.5 (3.9) days for trio exome, and 22.7 (3.9) days for critical trio exome. Clinical indications for exome sequencing included a range of medical concerns. Overall, a molecular diagnosis was achieved in 102 infants (36.7%) by clinical exome sequencing, with relatively low yield for cardiovascular abnormalities. The diagnosis affected medical management for 53 infants (52.0%) and had a substantial effect on informed redirection of care, initiation of new subspecialist care, medication/dietary modifications, and furthering life-saving procedures in select patients. Critical trio exome sequencing revealed a molecular diagnosis in 32 of 63 infants (50.8%) at a mean (SEM) of 33.1 (5.6) days of life with a mean (SEM) turnaround time of 13.0 (0.4) days. Clinical care was altered by the diagnosis in 23 of 32 patients (71.9%). The diagnostic yield, patient age at diagnosis, and medical effect in the group that underwent critical trio exome sequencing were significantly different compared with the group who underwent regular exome testing. For deceased infants (n = 81), genetic disorders were molecularly diagnosed in 39 (48.1%) by exome sequencing, with implications for recurrence risk counseling. Conclusions and Relevance: Exome sequencing is a powerful tool for the diagnostic evaluation of critically ill infants with suspected monogenic disorders in the neonatal and pediatric intensive care units and its use has a notable effect on clinical decision making.
Keywords: Adult; Critical Care; Disease Management; Exome; Genetic Counseling; Genetic Diseases, Inborn; Humans; Infant; Infant Care; Infant, Newborn; Intensive Care Units, Pediatric; Length of Stay; Retrospective Studies; Texas; Whole Exome Sequencing

De novo missense variants in PPP1CB are associated with intellectual disability and congenital heart disease. - Ma, Lijiang; Bayram, Yavuz; McLaughlin, Heather M; Cho, Megan T; Krokosky, Alyson; Turner, Clesson E; Lindstrom, Kristin; Bupp, Caleb P; Mayberry, Katey; Mu, Weiyi; Bodurtha, Joann; Weinstein, Veronique; et al. (Hum Genet, 2016)
Intellectual disabilities are genetically heterogeneous and can be associated with congenital anomalies. Using whole-exome sequencing (WES), we identified five different de novo missense variants in the protein phosphatase-1 catalytic subunit beta (PPP1CB) gene in eight unrelated individuals who share an overlapping phenotype of dysmorphic features, macrocephaly, developmental delay or intellectual disability (ID), congenital heart disease, short stature, and skeletal and connective tissue abnormalities. Protein phosphatase-1 (PP1) is a serine/threonine-specific protein phosphatase involved in the dephosphorylation of a variety of proteins. The PPP1CB gene encodes a PP1 subunit that regulates the level of protein phosphorylation. All five altered amino acids we observed are highly conserved among the PP1 subunit family, and all are predicted to disrupt PP1 subunit binding and impair dephosphorylation. Our data suggest that our heterozygous de novo PPP1CB pathogenic variants are associated with syndromic intellectual disability.
Keywords: Adolescent; Adult; Child; Child, Preschool; Exome; Female; Genetic Association Studies; Genetic Predisposition to Disease; Heart Defects, Congenital; Humans; Intellectual Disability; Male; Mutation, Missense; Phosphorylation; Protein Phosphatase 1

A genome-wide association study of congenital cardiovascular left-sided lesions shows association with a locus on chromosome 20. - Hanchard, Neil A; Swaminathan, Shanker; Bucasas, Kristine; Furthner, Dieter; Fernbach, Susan; Azamian, Mahshid S; Wang, Xueqing; Lewin, Mark; Towbin, Jeffrey A; D'Alessandro, Lisa C A; Morris, Shaine A; Dreyer, William; et al. (Hum Mol Genet, 2016)
Congenital heart defects involving left-sided lesions (LSLs) are relatively common birth defects with substantial morbidity and mortality. Previous studies have suggested a high heritability with a complex genetic architecture, such that only a few LSL loci have been identified. We performed a genome-wide case-control association study to address the role of common variants using a discovery cohort of 778 cases and 2756 controls. We identified a genome-wide significant association mapping to a 200 kb region on chromosome 20q11 [P= 1.72 × 10 for rs3746446; imputed Single Nucleotide Polymorphism (SNP) rs6088703 P= 3.01 × 10, odds ratio (OR)= 1.6 for both]. This result was supported by transmission disequilibrium analyses using a subset of 541 case families (lowest P in region= 4.51 × 10, OR= 1.5). Replication in a cohort of 367 LSL cases and 5159 controls showed nominal association (P= 0.03 for rs3746446) resulting in P= 9.49 × 10 for rs3746446 upon meta-analysis of the combined cohorts. In addition, a group of seven SNPs on chromosome 1q21.3 met threshold for suggestive association (lowest P= 9.35 × 10 for rs12045807). Both regions include genes involved in cardiac development-MYH7B/miR499A on chromosome 20 and CTSK, CTSS and ARNT on chromosome 1. Genome-wide heritability analysis using case-control genotyped SNPs suggested that the mean heritability of LSLs attributable to common variants is moderately high ([Formula: see text] range= 0.26-0.34) and consistent with previous assertions. These results provide evidence for the role of common variation in LSLs, proffer new genes as potential biological candidates, and give further insight to the complex genetic architecture of congenital heart disease.
Keywords: Chromosome Mapping; Chromosomes, Human, Pair 20; Cohort Studies; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Heart Defects, Congenital; Heart Ventricles; Humans; Male; Polymorphism, Single Nucleotide

MIPEP recessive variants cause a syndrome of left ventricular non-compaction, hypotonia, and infantile death. - Eldomery, Mohammad K; Akdemir, Zeynep C; Vögtle, F-Nora; Charng, Wu-Lin; Mulica, Patrycja; Rosenfeld, Jill A; Gambin, Tomasz; Gu, Shen; Burrage, Lindsay C; Al Shamsi, Aisha; Penney, Samantha; Jhangiani, Shalini N; et al. (Genome Med, 2016)
BACKGROUND: Mitochondrial presequence proteases perform fundamental functions as they process about 70 % of all mitochondrial preproteins that are encoded in the nucleus and imported posttranslationally. The mitochondrial intermediate presequence protease MIP/Oct1, which carries out precursor processing, has not yet been established to have a role in human disease. METHODS: Whole exome sequencing was performed on four unrelated probands with left ventricular non-compaction (LVNC), developmental delay (DD), seizures, and severe hypotonia. Proposed pathogenic variants were confirmed by Sanger sequencing or array comparative genomic hybridization. Functional analysis of the identified MIP variants was performed using the model organism Saccharomyces cerevisiae as the protein and its functions are highly conserved from yeast to human. RESULTS: Biallelic single nucleotide variants (SNVs) or copy number variants (CNVs) in MIPEP, which encodes MIP, were present in all four probands, three of whom had infantile/childhood death. Two patients had compound heterozygous SNVs (p.L582R/p.L71Q and p.E602*/p.L306F) and one patient from a consanguineous family had a homozygous SNV (p.K343E). The fourth patient, identified through the GeneMatcher tool, a part of the Matchmaker Exchange Project, was found to have inherited a paternal SNV (p.H512D) and a maternal CNV (1.4-Mb deletion of 13q12.12) that includes MIPEP. All amino acids affected in the patients' missense variants are highly conserved from yeast to human and therefore S. cerevisiae was employed for functional analysis (for p.L71Q, p.L306F, and p.K343E). The mutations p.L339F (human p.L306F) and p.K376E (human p.K343E) resulted in a severe decrease of Oct1 protease activity and accumulation of non-processed Oct1 substrates and consequently impaired viability under respiratory growth conditions. The p.L83Q (human p.L71Q) failed to localize to the mitochondria. CONCLUSIONS: Our findings reveal for the first time the role of the mitochondrial intermediate peptidase in human disease. Loss of MIP function results in a syndrome which consists of LVNC, DD, seizures, hypotonia, and cataracts. Our approach highlights the power of data exchange and the importance of an interrelationship between clinical and research efforts for disease gene discovery.
Keywords: Adult; Amino Acid Sequence; Female; Genes, Recessive; Heart Defects, Congenital; Humans; Infant; Infant, Newborn; Male; Metalloendopeptidases; Muscle Hypotonia; Pedigree; Phenotype; Sequence Homology, Amino Acid; Sudden Infant Death; Syndrome

Recurrent Muscle Weakness with Rhabdomyolysis, Metabolic Crises, and Cardiac Arrhythmia Due to Bi-allelic TANGO2 Mutations. - Lalani, Seema R; Liu, Pengfei; Rosenfeld, Jill A; Watkin, Levi B; Chiang, Theodore; Leduc, Magalie S; Zhu, Wenmiao; Ding, Yan; Pan, Shujuan; Vetrini, Francesco; Miyake, Christina Y; Shinawi, Marwan; et al. (Am J Hum Genet, 2016)
The underlying genetic etiology of rhabdomyolysis remains elusive in a significant fraction of individuals presenting with recurrent metabolic crises and muscle weakness. Using exome sequencing, we identified bi-allelic mutations in TANGO2 encoding transport and Golgi organization 2 homolog (Drosophila) in 12 subjects with episodic rhabdomyolysis, hypoglycemia, hyperammonemia, and susceptibility to life-threatening cardiac tachyarrhythmias. A recurrent homozygous c.460G>A (p.Gly154Arg) mutation was found in four unrelated individuals of Hispanic/Latino origin, and a homozygous ∼34 kb deletion affecting exons 3-9 was observed in two families of European ancestry. One individual of mixed Hispanic/European descent was found to be compound heterozygous for c.460G>A (p.Gly154Arg) and the deletion of exons 3-9. Additionally, a homozygous exons 4-6 deletion was identified in a consanguineous Middle Eastern Arab family. No homozygotes have been reported for these changes in control databases. Fibroblasts derived from a subject with the recurrent c.460G>A (p.Gly154Arg) mutation showed evidence of increased endoplasmic reticulum stress and a reduction in Golgi volume density in comparison to control. Our results show that the c.460G>A (p.Gly154Arg) mutation and the exons 3-9 heterozygous deletion in TANGO2 are recurrent pathogenic alleles present in the Latino/Hispanic and European populations, respectively, causing considerable morbidity in the homozygotes in these populations.
Keywords: Alleles; Arabs; Arrhythmias, Cardiac; Base Sequence; Child; Child, Preschool; Endoplasmic Reticulum Stress; European Continental Ancestry Group; Exome; Exons; Female; Gene Deletion; Golgi Apparatus; Hispanic Americans; Homozygote; Humans; Infant; Male; Molecular Sequence Data; Muscle Weakness; Pedigree; Rhabdomyolysis

De Novo GMNN Mutations Cause Autosomal-Dominant Primordial Dwarfism Associated with Meier-Gorlin Syndrome. - Burrage, Lindsay C; Charng, Wu-Lin; Eldomery, Mohammad K; Willer, Jason R; Davis, Erica E; Lugtenberg, Dorien; Zhu, Wenmiao; Leduc, Magalie S; Akdemir, Zeynep C; Azamian, Mahshid; Zapata, Gladys; Hernandez, Patricia P; et al. (Am J Hum Genet, 2015)
Meier-Gorlin syndrome (MGS) is a genetically heterogeneous primordial dwarfism syndrome known to be caused by biallelic loss-of-function mutations in one of five genes encoding pre-replication complex proteins: ORC1, ORC4, ORC6, CDT1, and CDC6. Mutations in these genes cause disruption of the origin of DNA replication initiation. To date, only an autosomal-recessive inheritance pattern has been described in individuals with this disorder, with a molecular etiology established in about three-fourths of cases. Here, we report three subjects with MGS and de novo heterozygous mutations in the 5' end of GMNN, encoding the DNA replication inhibitor geminin. We identified two truncating mutations in exon 2 (the 1(st) coding exon), c.16A>T (p.Lys6(∗)) and c.35_38delTCAA (p.Ile12Lysfs(∗)4), and one missense mutation, c.50A>G (p.Lys17Arg), affecting the second-to-last nucleotide of exon 2 and possibly RNA splicing. Geminin is present during the S, G2, and M phases of the cell cycle and is degraded during the metaphase-anaphase transition by the anaphase-promoting complex (APC), which recognizes the destruction box sequence near the 5' end of the geminin protein. All three GMNN mutations identified alter sites 5' to residue Met28 of the protein, which is located within the destruction box. We present data supporting a gain-of-function mechanism, in which the GMNN mutations result in proteins lacking the destruction box and hence increased protein stability and prolonged inhibition of replication leading to autosomal-dominant MGS.
Keywords: Adolescent; Amino Acid Sequence; Base Sequence; Cell Cycle; Child, Preschool; Congenital Microtia; Dwarfism; Exons; Female; Geminin; Gene Expression; Genes, Dominant; Growth Disorders; Heterozygote; High-Throughput Nucleotide Sequencing; Humans; Inheritance Patterns; Male; Micrognathism; Molecular Sequence Data; Mutation; Patella; Pedigree; Protein Stability; Proteolysis; RNA Splicing; Sequence Alignment

Mutations in PURA cause profound neonatal hypotonia, seizures, and encephalopathy in 5q31.3 microdeletion syndrome. - Lalani, Seema R; Zhang, Jing; Schaaf, Christian P; Brown, Chester W; Magoulas, Pilar; Tsai, Anne Chun-Hui; El-Gharbawy, Areeg; Wierenga, Klaas J; Bartholomew, Dennis; Fong, Chin-To; Barbaro-Dieber, Tina; Kukolich, Mary K; et al. (Am J Hum Genet, 2014)
5q31.3 microdeletion syndrome is characterized by neonatal hypotonia, encephalopathy with or without epilepsy, and severe developmental delay, and the minimal critical deletion interval harbors three genes. We describe 11 individuals with clinical features of 5q31.3 microdeletion syndrome and de novo mutations in PURA, encoding transcriptional activator protein Pur-α, within the critical region. These data implicate causative PURA mutations responsible for the severe neurological phenotypes observed in this syndrome.
Keywords: Abnormalities, Multiple; Amino Acid Sequence; Animals; Base Sequence; Caenorhabditis elegans; Chromosome Deletion; Chromosome Mapping; Chromosomes, Human, Pair 5; DNA-Binding Proteins; Humans; Molecular Sequence Data; Muscle Hypotonia; Mutation; Seizures; Sequence Analysis, DNA; Syndrome; Transcription Factors

Parental somatic mosaicism is underrecognized and influences recurrence risk of genomic disorders. - Campbell, Ian M; Yuan, Bo; Robberecht, Caroline; Pfundt, Rolph; Szafranski, Przemyslaw; McEntagart, Meriel E; Nagamani, Sandesh C S; Erez, Ayelet; Bartnik, Magdalena; Wiśniowiecka-Kowalnik, Barbara; Plunkett, Katie S; Pursley, Amber N; et al. (Am J Hum Genet, 2014)
New human mutations are thought to originate in germ cells, thus making a recurrence of the same mutation in a sibling exceedingly rare. However, increasing sensitivity of genomic technologies has anecdotally revealed mosaicism for mutations in somatic tissues of apparently healthy parents. Such somatically mosaic parents might also have germline mosaicism that can potentially cause unexpected intergenerational recurrences. Here, we show that somatic mosaicism for transmitted mutations among parents of children with simplex genetic disease is more common than currently appreciated. Using the sensitivity of individual-specific breakpoint PCR, we prospectively screened 100 families with children affected by genomic disorders due to rare deletion copy-number variants (CNVs) determined to be de novo by clinical analysis of parental DNA. Surprisingly, we identified four cases of low-level somatic mosaicism for the transmitted CNV in DNA isolated from parental blood. Integrated probabilistic modeling of gametogenesis developed in response to our observations predicts that mutations in parental blood increase recurrence risk substantially more than parental mutations confined to the germline. Moreover, despite the fact that maternally transmitted mutations are the minority of alleles, our model suggests that sexual dimorphisms in gametogenesis result in a greater proportion of somatically mosaic transmitting mothers who are thus at increased risk of recurrence. Therefore, somatic mosaicism together with sexual differences in gametogenesis might explain a considerable fraction of unexpected recurrences of X-linked recessive disease. Overall, our results underscore an important role for somatic mosaicism and mitotic replicative mutational mechanisms in transmission genetics.
Keywords: Cell Division; DNA Copy Number Variations; Female; Gametogenesis; Genetic Diseases, Inborn; Genomics; Germ Cells; Germ-Line Mutation; Humans; Male; Models, Genetic; Mosaicism; Mutation; Pedigree; Prospective Studies; Recurrence; Risk; Sex Characteristics; Smith-Magenis Syndrome

Deletions of recessive disease genes: CNV contribution to carrier states and disease-causing alleles. - Boone, Philip M; Campbell, Ian M; Baggett, Brett C; Soens, Zachry T; Rao, Mitchell M; Hixson, Patricia M; Patel, Ankita; Bi, Weimin; Cheung, Sau Wai; Lalani, Seema R; Beaudet, Arthur L; Stankiewicz, Pawel; et al. (Genome Res, 2013)
Over 1200 recessive disease genes have been described in humans. The prevalence, allelic architecture, and per-genome load of pathogenic alleles in these genes remain to be fully elucidated, as does the contribution of DNA copy-number variants (CNVs) to carrier status and recessive disease. We mined CNV data from 21,470 individuals obtained by array-comparative genomic hybridization in a clinical diagnostic setting to identify deletions encompassing or disrupting recessive disease genes. We identified 3212 heterozygous potential carrier deletions affecting 419 unique recessive disease genes. Deletion frequency of these genes ranged from one occurrence to 1.5%. When compared with recessive disease genes never deleted in our cohort, the 419 recessive disease genes affected by at least one carrier deletion were longer and located farther from known dominant disease genes, suggesting that the formation and/or prevalence of carrier CNVs may be affected by both local and adjacent genomic features and by selection. Some subjects had multiple carrier CNVs (307 subjects) and/or carrier deletions encompassing more than one recessive disease gene (206 deletions). Heterozygous deletions spanning multiple recessive disease genes may confer carrier status for multiple single-gene disorders, for complex syndromes resulting from the combination of two or more recessive conditions, or may potentially cause clinical phenotypes due to a multiply heterozygous state. In addition to carrier mutations, we identified homozygous and hemizygous deletions potentially causative for recessive disease. We provide further evidence that CNVs contribute to the allelic architecture of both carrier and recessive disease-causing mutations. Thus, a complete recessive carrier screening method or diagnostic test should detect CNV alleles.
Keywords: Alleles; Comparative Genomic Hybridization; Databases, Genetic; DNA Copy Number Variations; Gene Deletion; Gene Frequency; Genes, Dominant; Genes, Recessive; Genetic Diseases, Inborn; Homozygote; Humans

TM4SF20 ancestral deletion and susceptibility to a pediatric disorder of early language delay and cerebral white matter hyperintensities. - Wiszniewski, Wojciech; Hunter, Jill V; Hanchard, Neil A; Willer, Jason R; Shaw, Chad; Tian, Qi; Illner, Anna; Wang, Xueqing; Cheung, Sau W; Patel, Ankita; Campbell, Ian M; Gelowani, Violet; et al. (Am J Hum Genet, 2013)
White matter hyperintensities (WMHs) of the brain are important markers of aging and small-vessel disease. WMHs are rare in healthy children and, when observed, often occur with comorbid neuroinflammatory or vasculitic processes. Here, we describe a complex 4 kb deletion in 2q36.3 that segregates with early childhood communication disorders and WMH in 15 unrelated families predominantly from Southeast Asia. The premature brain aging phenotype with punctate and multifocal WMHs was observed in ~70% of young carrier parents who underwent brain MRI. The complex deletion removes the penultimate exon 3 of TM4SF20, a gene encoding a transmembrane protein of unknown function. Minigene analysis showed that the resultant net loss of an exon introduces a premature stop codon, which, in turn, leads to the generation of a stable protein that fails to target to the plasma membrane and accumulates in the cytoplasm. Finally, we report this deletion to be enriched in individuals of Vietnamese Kinh descent, with an allele frequency of about 1%, embedded in an ancestral haplotype. Our data point to a constellation of early language delay and WMH phenotypes, driven by a likely toxic mechanism of TM4SF20 truncation, and highlight the importance of understanding and managing population-specific low-frequency pathogenic alleles.
Keywords: Age of Onset; Aging, Premature; Asian Continental Ancestry Group; Base Sequence; Brain; Child; Child, Preschool; Chromosomes, Human, Pair 2; Exons; Female; Genetic Predisposition to Disease; Humans; Language Development Disorders; Leukoencephalopathies; Magnetic Resonance Imaging; Male; Molecular Sequence Data; Pedigree; Sequence Analysis, DNA; Sequence Deletion; Tetraspanins